What is the best time interval for health status assessments after discharge? Findings from the E-INH study. (3rd October 2022) - Kerwagen, F; Sahiti, F; Sehner, S; Albert, J; Cejka, V; Moser, N; Morbach, C; Gueder, G; Frantz, S; Ertl, G; Angermann, C E; Stoerk, S
Abstract: Background: The association of clinically meaningful changes in the Kansas City Cardiomyopathy Questionnaire Overall Summary score (KCCQ-os) with prognosis in patients with heart failure (HF) is well established. However, most studies have considered several weeks as time intervals for the serial assessments of the KCCQ-os. Therefore, we sought to investigate the changes of the KCCQ-os and their prognostic relevance between discharge and several months. Methods: We assessed serial KCCQ data from the Extended Interdisciplinary Network Heart Failure (E-INH) study: between 2004 and 2007, 1022 hospitalized HF patients with a left ventricular ejection fraction (LVEF) <40% were randomized into the remote care program HeartNetCare-HF™ (HNC) or usual care (UC). Changes of the KCCQ-os were calculated from baseline to 6 months, baseline to 12 months and baseline to 18 months, and compared by repeated measure ANOVA. We used the established thresholds of 5, 10 and 20 points for the differentiation of clinically meaningful changes as well as 5-point decrements of KCCQ-os for prognostic analyses. The association of change in KCCQ-os with long-term survival was assessed using Kaplan-Meier curves and Cox proportional hazard models. Results: Of 1022 participants, 604 patients (59%) provided complete serial KCCQ data sets at baseline and after 6, 12, and 18 months: mean (SD) age 65.6 (12.2) years, 24% women, median (quartiles) KCCQ-os at baseline 59.2 (43.2; 77.1). 345 (57%) patients died, median follow-up time 8.9 years (4.1; 10.0). There were significant median changes of KCCQ-os from baseline over time: 6-month 9.9 (−0.8; 26.8), 12-month 12.5 (−1.5; 29.4), and 18-month 13.4 (−1.1; 33.7), respectively (all p<0.05). As shown in figure 1, the percentage of patients with large improvements or large deteriorations (each ≥20 points) increased over time. In Kaplan-Meier survival analysis, changes of KCCQ-os according to the established thresholds were not significant at 6 months, but after 12 and 18 months (see table 1). Each 5-point decrement of KCCQ-os observed after 6, 12, or 18 months predicted all-cause death after 10 years of follow-up: HR, 1.11 (95% CI 1.04–1.17), HR 1.11 (95% CI 1.05–1.17), and HR 1.11 (95% CI 1.05–1.17), respectively. Adjustment for age, sex and KCCQ-os at baseline did not materially alter these associations: HR 1.17 (95% CI 1.11–1.24), HR 1.16 (95% CI 1.09–1.22), and HR 1.19 (95% CI 1.12–1.26), respectively. Conclusion: Amongst patients with HF surviving at least 18 months after being hospitalized for decompensated HF, a change in KCCQ-os identified patients at increased risk in the years to come. This association was apparent regardless of the time point of score collection. Since Patient-Reported Outcomes as the KCCQ may be easily collected via phone or a medical application, our findings not only confirm the prognostic utility of serial health status assessments but also might be useful to triage the frequency of clinical follow-ups. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): BMBF